Efeito do armazenamento no perfil sensorial do açúcar mascavo - Souza, Yara Karolina Moura de (2023)
The stability and quality of sugar during storage are related to microbiological and physicochemical parameters. Due to its production process, raw sugar typically has higher moisture content when compared with other sugars. It can alter the appearance and texture of the product. This study aimed to evaluate the influence of storage on the sensory characteristics of raw sugar with different moisture levels and particle sizes, seeking to determine whether the sensory quality of the product would be altered. The sugar was produced using the SP80-3280 variety, with four samples: A=1.69, B=1.96, C=2.00, and D=4.13% moisture content. Moisture analysis, water activity, total coliforms, conductometric ashes, and instrumental color analysis were performed. For the sensory analysis, a quantitative descriptive method was used to describe appearance and texture attributes. The instrumental color analysis regarding luminosity showed that there was no significant change for sample A over a period of 365 days. Sample D was considered the darkest. The sugars showed positive a* and b* parameters. Samples A, B, and C showed an increase in chroma values; all samples decreased their values in the hue parameter. As for statistical analyses, analysis of variance was used followed by Tukey's test and Principal Component Analysis (PCA). The moisture analysis of sample D (4.13%) was considered the most humid and with the highest water activity. In the analysis of total coliforms, all samples were within the standard. In the sensory analysis, the sensory attributes were: brown color, color homogeneity, homogeneous appearance, wet appearance, wet texture and grainy texture. Regarding ADQ, sugar D was considered the darkest, while samples B, C and D more homogeneous in terms of color and appearance, samples B and C were the least grainy and samples B and C were considered to have a more humid texture. Sugar A was the least accepted and purchase intention was greater for Sugar D followed by sugar A. Samples D and C were the darkest and most accepted for the color attribute, while samples A and B were the least accepted. Therefore, it was found that storage influenced the physical-chemical parameters, sensory attributes of the descriptive analysis and acceptance test, but not enough to compromise the quality and safety of the product.